Intracranial immature teratoma invading the nasal cavity mimicking olfactory neuroblastoma: A case report. Issue 28 (July 2018) - Jiang, Yuefeng; Mao, Xiaoyun; Zhao, Yang; Fan, Chuifeng
Abstract: Rationale: Primary intracranial immature teratoma accounts for majority of congenital central nervous system germ-cell tumors, but it is extremely rare in patients older than 15 years. Patient concerns: A 27-year-old woman was referred to our hospital for headache, nasal congestion, and decreased olfactory sensation. Imaging showed a mass measuring approximately 5 cm × 4 cm in the right frontal lobe, which also filled the right nasal cavity. Histopathologically, the intracranial tumor tissues were composed of both mature tissues, including glands and squamous epithelial cells and immature neuroectodermal components. However, the tumor tissues in the nasal cavity were mainly immature neuroectodermal components that mimicked olfactory neuroblastoma. The cells stained positively for neuron-specific enolase, Alpha Thalassemia/Mental Retardation Syndrome X-Linked, and Oligodendrocyte transcription factor on immunostaining, proving a neuroectodermal differentiation. Diagnoses: According to these findings, the tumor was diagnosed as a primary intracranial immature teratoma that also involved the nasal cavity after excluding the metastatic tumors. Interventions: The patient underwent 2 surgeries. The first surgery was via the subfrontal approach, followed by a second endoscopic sinus surgery performed 22 days later. Outcomes: The patient had no recurrence within a 6-month follow-up after the last surgery. Lessons: When an intracranial immature teratoma involves the nasal cavity, the lesions in the nasal cavity may mimic other tumors including olfactory neuroblastoma. We suggest that thorough examination of tumor tissues and identification of variable components are critical for the appropriate diagnosis of intracranial immature teratoma, a rare tumor.